Constraints in Production and Marketing of Ginger in state of Telangana, India - , Suday Shivani, T. Lavanya, B. Sowjanya; B.Savitha (Archives of Current Research International, 2024)
Aim: The study has been taken to identify and analyze the reasons for decline in area and production of Ginger and problems faced by the farmers in cultivation of ginger in state of Telangana. By understanding these problems, the study seeks to provide insights for decline in area under Ginger cultivation and provide recommendations to the Ginger farmers to overcome the problems faced in production and marketing of ginger in study area. Study Design: Ex-Posto Facto research design was used for the study. Place and Duration of Study: The study was conducted in Sangareddy district of Telangana, where ginger has been cultivated as a traditional crop for more than 20 years. Within the district, two mandals with the highest area under ginger cultivation were selected for the study. The study period is from 2023- 2024. Methodology: A multi-stage random sampling technique was employed for the study, with a sample size of 60 farmers. The farmers were interviewed personally through a well-structured and pre-tested schedule and Garrett’s ranking technique was used to rank the problems. Results: The results of the study revealed that farmers were facing problems in the production and marketing of Ginger. Incidence of pests and diseases was the major problem and ranked as the first constraint which was followed by high cost of seed and non -availability of quality seed at village level, high cost of FYM and fertilizers, labour shortage and high cost of labour during peak season, un-favourable weather conditions etc. are identified as the other major production constraints. Whereas in marketing of Ginger, high Price fluctuations was identified as the major constraint followed by high charges by commission agents, lack of market infrastructure, high marketing costs etc. Conclusion: To increase the area under ginger and enhance the profitability of ginger farming, it is essential to address these constraints through targeted interventions and support systems. Improving market infrastructure and reducing intermediary costs are also vital steps toward stabilizing prices and boosting farmers incomes. Solving these complex issues will necessitate collaborative efforts from stakeholders throughout the agricultural value chain.